1987
DOI: 10.1161/01.res.60.5.700
|View full text |Cite
|
Sign up to set email alerts
|

Elevation in cytosolic free calcium concentration early in myocardial ischemia in perfused rat heart.

Abstract: Changes in cytosolic free calcium concentration during myocardial ischemia were measured by 19F NMR in 5FBAPTA-loaded perfused rat hearts. The hearts were perfused with Krebs-Henseleit buffer containing 5 microM of the acetoxymethyl ester of 5FBAPTA, which was hydrolyzed by cytosolic esterases to achieve cytosolic concentrations of 5FBAPTA of 0.12 to 0.65 mM. Cytosolic free calcium concentrations were calculated as the product of the ratio of peak areas for bound and free 5FBAPTA in the NMR spectra and the dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
165
2
4

Year Published

1988
1988
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 453 publications
(180 citation statements)
references
References 26 publications
9
165
2
4
Order By: Relevance
“…Our results are in agreement with ®ndings of previous studies showing a transcriptional and translational up-regulation of calpain I in the non-infarcted hypertrophied rat myocardium (Sandmann et al, 2001). Additionally, studies on rats demonstrated an increase in diastolic myocardial [Ca 2+ ] i in ventricular myocytes of the failing heart which were associated with cardiac hypertrophy following pressure overload (Gwathmey & Morgan, 1985;Steenbergen et al, 1987b) and MI (Sandmann et al, 1999). This might be related to an increased Ca 2+ -inward movement (Elliott et al, 1989;Sipido et al, 2000) and/or to a reduced Ca 2+ -reuptake by the sarcoplasmatic reticulum (SR) (De la Bastie et al, 1990;O'Rourke et al, 1999;Szymanska et al, 2000).…”
Section: Calpain I In the Non-infarcted Myocardium Post Misupporting
confidence: 93%
“…Our results are in agreement with ®ndings of previous studies showing a transcriptional and translational up-regulation of calpain I in the non-infarcted hypertrophied rat myocardium (Sandmann et al, 2001). Additionally, studies on rats demonstrated an increase in diastolic myocardial [Ca 2+ ] i in ventricular myocytes of the failing heart which were associated with cardiac hypertrophy following pressure overload (Gwathmey & Morgan, 1985;Steenbergen et al, 1987b) and MI (Sandmann et al, 1999). This might be related to an increased Ca 2+ -inward movement (Elliott et al, 1989;Sipido et al, 2000) and/or to a reduced Ca 2+ -reuptake by the sarcoplasmatic reticulum (SR) (De la Bastie et al, 1990;O'Rourke et al, 1999;Szymanska et al, 2000).…”
Section: Calpain I In the Non-infarcted Myocardium Post Misupporting
confidence: 93%
“…Subsequently, several studies*" 7 demonstrated that calcium channel antagonist agents protect against ventricular fibrillation during acute myocardial ischemia and following reperfusion of the acutely ischemic myocardium. In a recent communication, Steenbergen and coworkers 8 showed cytosolic free calcium to be increased within 10 minutes of acute global ischemia in the perfused rat heart. Definitive evidence has been presented that cytosolic calcium is increased within 10 minutes of reperfusion of the acutely ischemic cat heart.…”
mentioning
confidence: 97%
“…Steenbergen et al 28 investigated the ionic alterations in perfused hearts of rats undergoing preconditioning. The 2 study groups underwent 30min of global ischemia, and one of the groups was treated with 4 periods of 5-min ischemia with 5-min intervals of reperfusion (preconditioning) at 37 o C between them.…”
Section: Groupmentioning
confidence: 99%
“…Murry et al 8 reported that after 40min of ischemia, the production of lactate in preconditioned hearts was 40% lower than that in nontreated hearts. Steenbergen et al 28 suggest that this reduction in the production of lactate may be due to a lower acidification of the intracellular medium. A lower concentration of hydrogen may reduce intracellular sodium and calcium increase through Na + -H + and Na + -Ca +2 exchangers, respectively.…”
Section: Groupmentioning
confidence: 99%